Baby pangolins on my plate: possible lessons to learn from the COVID-19 pandemic - Gabriele Volpato; Michele F. Fontefrancesco; Paolo Gruppuso; Dauro M. Zocchi; Andrea Pieroni (BMC, 2020)
Abstract The Journal of Ethnobiology and Ethnomedicine (JEET), throughout its 15 years of existence, has tried to provide a respected outlet for scientific knowledge concerning the inextricable links between human societies and nature, food, and health. Ethnobiology and ethnomedicine-centred research has moved at the (partially artificial and fictitious) interface between nature and culture and has investigated human consumption of wild foods and wild animals, as well as the use of wild animals or their parts for medicinal and other purposes, along with the associated knowledge, skills, practices, and beliefs. Little attention has been paid, however, to the complex interplay of social and cultural reasons behind the increasing pressure on wildlife. The available literature suggest that there are two main drivers that enhance the necessary conditions for infectious diseases to cross the species barrier from wild animals to humans: (1) the encroachment of human activities (e.g., logging, mining, agricultural expansion) into wild areas and forests and consequent ecological disruptions; and, connected to the former, (2) the commodification of wild animals (and natural resources in general) and an expanding demand and market for wild meat and live wild animals, particularly in tropical and sub-tropical areas. In particular, a crucial role may have been played by the bushmeat-euphoria and attached elitist gastronomies and conspicuous consumption phenomena. The COVID-19 pandemic will likely require ethnobiologists to reschedule research agendas and to envision new epistemological trajectories aimed at more effectively mitigating the mismanagement of natural resources that ultimately threats our and other beings' existence.